L’arte della conversazione. Alla ricerca del sacrificio perduto: da Tylor a Freud (1870-1913) - Cristiana Facchini (Storicamente)
Theories of religion, which appeared in the second half of the Nineteenth century, focused their attention on the analysis of sacrifice. The theorizing process that is so distinctive of this period contributed to define a number of relevant concepts that exerted a relevant influence in the Twentieth century. This article aims to illustrate the path which led to relevant theories of sacrifice unearthing the conversation among some scholars and intellectuals of different European countries whose work contributed to the rise and institutionalization of new disciplinary fields: sociology, anthropology, ethnology, history of religions, psychoanalysis.